A BPA Approach to the Shroud of Turin1. Issue 1 (10th July 2018) - Borrini, Matteo; Garlaschelli, Luigi
Abstract: An investigation into the arm and body position required to obtain the blood pattern visible in the image of the Shroud of Turin was performed using a living volunteer. The two short rivulets on the back of the left hand of the Shroud are only consistent with a standing subject with arms at a ca 45° angle. This angle is different from that necessary for the forearm stains, which require nearly vertical arms for a standing subject. The BPA of blood visible on the frontal side of the chest (the lance wound) shows that the Shroud represents the bleeding in a realistic manner for a standing position while the stains at the back—of a supposed postmortem bleeding from the same wound for a supine corpse—are totally unrealistic. Simulation of bleeding from the nail wounds contacting wood surfaces yielded unclear results.